Glycosylation is key for enhancing drug recognition into spike glycoprotein of SARS-CoV-2. (June 2022) - Ropón-Palacios, Georcki; Pérez-Silva, Jhon; Rojas-Humpire, Ricardo; Olivos-Ramírez, Gustavo E.; Chenet-Zuta, Manuel; Cornejo-Villanueva, Victor; Carmen-Sifuentes, Sheyla; Otazu, Kewin; Ramirez-Díaz, Yaritza L.; Chozo, Karolyn Vega; Camps, Ihosvany
Abstract: The emergence of COVID-19 caused by SARS-CoV-2 and its spread since 2019 represents the major public health problem worldwide nowadays, which has generated a high number of infections and deaths. The spike protein (S protein) is the most studied protein of SARS-CoV-2, and key to host-cell entry through ACE2 receptor. This protein presents a large pattern of glycosylations with important roles in immunity and infection mechanisms. Therefore, understanding key aspects of the molecular mechanisms of these structures, during drug recognition in SARS-CoV-2, may contribute to therapeutic alternatives. In this work, we explored the impact of glycosylations on the drug recognition on two domains of the S protein, the receptor-binding domain (RBD) and the N-terminal domain (NTD) through molecular dynamics simulations and computational biophysics analysis. Our results show that glycosylations in the S protein induce structural stability and changes in rigidity/flexibility related to the number of glycosylations in the structure. These structural changes are important for its biological activity as well as the correct interaction of ligands in the RBD and NTD regions. Additionally, we evidenced a roto-translation phenomenon in the interaction of the ligand with RBD in the absence of glycosylation, which disappears due to the influence of glycosylation and the convergence of metastable states in RBM. Similarly, glycosylations in NTD promote an induced fit phenomenon, which is not observed in the absence of glycosylations; this process is decisive for the activity of the ligand at the cryptic site. Altogether, these results provide an explanation of glycosylation relevance in biophysical properties and drug recognition to S protein of SARS-CoV-2, which must be considered in the rational drug development and virtual screening targeting S protein. Graphical Abstract: ga1 Highlights: Glycosylations play an important role in the biophysical structural properties in S protein of SARS-CoV-2. Biophysical changes enhance drug recognition in RBD and NTD, key structures for the development of new drugs. Induction of structural stability and local changes in rigidity/flexibility related to the number of glycosylations. · Structural changes and induced fit are evidenced in the interaction of ligands in the absence/presence of glycosylation.